2020
DOI: 10.21203/rs.3.rs-56735/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acupuncture protects against cerebral ischemia-reperfusion injury via suppressing endoplasmic reticulum stress-mediated autophagy and apoptosis

Abstract: Background: Acupuncture treatment possesses the neuroprotection potential to attenuate cerebral ischemia-reperfusion (I/R) injury. Endoplasmic reticulum (ER) stress has been suggested to be involved in the pathogenic mechanism of cerebral I/R injury. Whether acupuncture protects against cerebral I/R injury via regulating ER stress remains unclear. This study aimed to evaluate the role of ER stress in the neuroprotection of acupuncture against cerebral I/R injury and its underlying mechanisms. Methods: Cerebral… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…13 Meanwhile, rapamycin is a known and efficacious mTOR inhibitor. 11 Recently, researchers confirmed 14,15 that acupuncture could induce or inhibit autophagy by improving endoplasmic reticulum stress (ERS) and regulating specific autophagy pathways, thus preserving nerve function and ameliorating neurological diseases. However, the specific mechanism remains unclear in acupuncture regulating autophagy to provide a neuroprotective effect after TBI.…”
Section: Introductionmentioning
confidence: 99%
“…13 Meanwhile, rapamycin is a known and efficacious mTOR inhibitor. 11 Recently, researchers confirmed 14,15 that acupuncture could induce or inhibit autophagy by improving endoplasmic reticulum stress (ERS) and regulating specific autophagy pathways, thus preserving nerve function and ameliorating neurological diseases. However, the specific mechanism remains unclear in acupuncture regulating autophagy to provide a neuroprotective effect after TBI.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have shown that autophagy plays an important role during cerebral I/R injury and is frequently mediated by oxidative stress, endoplasmic reticulum stress, and other reactions in cells after MCAO/R [ 24 , 25 ]. BHD plays a protective role against ischemic stroke with multiple targets, such as oxidative stress, endoplasmic reticulum stress, inflammation, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological score (mNSS) was detected as described in a previous study by a researcher blind to the treatment groups before the rats were killed by rapid cervical dislocation 34 . Scores ranging from 0–18 (0 was considered as normal, whereas 18 represented the maximum nerve function defect) were given for four tests, including movement, sensation, balance beam, and reflex.…”
Section: Methodsmentioning
confidence: 99%